Sustainable cultivation of microalgae biomass for bioenergy production - Peter, Angela Paul (2022)
This thesis mainly focuses on solving the challenges faced in the production of sustainable growth medium of microalgae and exploiting the potential techniques on 16 digitalization of microalgae growth monitoring. Five technical problem statements have been examined throughout the process which is essential in upscaling the growth of microalgae production plant. The problem statements rectified in this research are: (1) Recognising the best organic medium to replace chemical based culture medium: evaluate the nutrient content of dairy food processing waste remediation to be integrated with microalgae culture system for the growth of biomass; (2) Identifying the optimised, organic medium culture with chemical based nutrient based on vision imaging systems for biomass growth monitoring; (3) Analysing the feasibility of the bioprocess recommended using life cycle analysis assessment of Chlorella vulgaris cultivation process using industrial waste powder as nutrient source in large scale. (4) Minimising the tedious lab growth monitoring system using UV-Vis: developed a mobile application (FindAlgae) for microalgae growth monetarization based on vision imaging system; and (5) Test run the functionality of the FindAlgae app by evaluating and optimising the recycling of culture medium in semi-continuous cultivation; biomass growth monitoring based on the developed mobile application (FindAlgae).